Pengaruh Corporate Social Responsibility dan Intellectual Capital Pada Kinerja Keuangan - Cahyani Prastuti, Made; Budiasih, I G.A.N. (E-Jurnal Akuntansi; Vol 27 No 2 (2019)DO - 10.24843/EJA.2019.v27.i02.p20, 2019)
The aim of this research is to know the influence of corporate social responsibility and intellectual capital on financial performance. Theories used are stakeholder, legitimacy, and resource-based theory. This research conducted on trading companies listed on the Indonesia Stock Exchange in 2015-2017. The samples taken were 26 companies, by non-probability sampling method with purposive sampling technique. Data collected through non-participant observation. The analysis techniques used are descriptive statistical analysis, classical assumptions, and multiple linear analysis. Based on the analysis found that corporate social responsibility has no effect on financial performance. This indicates that the high and low disclosure of CSR will not affect the financial performance of the trade sector. The second hypothesis states that intellectual capital has a positive effect on financial performance. This indicates that the higher the intellectual capital, the higher the financial performance of the company. Combination of intellectual capital can enhance competitive advantage for companies. Keywords: Financial performance, corporate social responsibility, intellectual capital